Demineralized bone matrix fibers formable as general and custom 3D printed mold-based implants for promoting bone regeneration. (26th July 2016) - Rodriguez, Rudy U; Kemper, Nathan; Breathwaite, Erick; Dutta, Sucharita M; Huber, Alexander; Murchison, Angela; Chen, Silvia; Hsu, Erin L; Hsu, Wellington K; Francis, Michael P
Abstract: Introduction. Bone repair frequently requires time-consuming implant construction, particularly when using un-formed implants with poor handling properties. We therefore developed osteoinductive, micro-fibrous surface patterned demineralized bone matrix (DBM) fibers for engineering both defect-matched and general three-dimensional implants. Methods and results. Implant molds were filled with demineralized human cortical bone fibers there were compressed and lyophilized, forming mechanically strong shaped DBM scaffolds. Enzyme linked immunosorbent assays and mass spectrometry confirmed that DBM fibers contained abundant osteogenic growth factors (bone morphogenetic proteins, insulin-like growth factor-I) and extracellular matrix proteins. Mercury porosimetry and mechanical testing showed interconnected pores within the mechanically stable, custom DBM fiber scaffolds. Mesenchymal stem cells readily attached to the DBM and showed increasing metabolic activity over time. DBM fibers further increased alkaline phosphatase activity in C2C12 cells. In vivo, DBM implants elicited osteoinductive potential in a mouse muscle pouch, and also promoted spine fusion in a rat arthrodesis model. Significance. DBM fibers can be engineered into custom-shaped, osteoinductive and osteoconductive implants with potential for repairing osseous defects with precise fitment, potentially reducing operating time. By providing pre-formed and custom implants, this regenerative allograft may improve patient outcomes following surgical bone repair, while further advancing personalized orthopedic and craniomaxillofacial medicine using three-dimensional-printed tissue molds.